Avaliação da Política Pública de Resíduos Sólidos no município de Sobral - Bezerra, Caroline Silva (2024)
This research evaluates the implementation of the Solid Waste Public Policy in the municipality of Sobral, based on Law No. 1789/2018 and the National Solid Waste Policy (PNRS), established by Law No. 12.305/2010. Using an in-depth evaluation approach, the study aims to understand the political-institutional context in which the policy has been implemented, its consolidation trajectory, and the residents' perceptions of its daily application. While there have been advances through initiatives such as the installation of eco-islands, the availability of electric tricycles for waste collection, and the implementation of environmental programs and actions, challenges persist, including public resistance and irregular waste disposal. The research investigates the causes of these contradictions by analyzing socioeconomic, cultural, and institutional dimensions, assessing the challenges in implementing the Solid Waste Policy in Sobral, identifying gaps, and proposing solutions to enhance waste management in alignment with national and international sustainability guidelines. The methodology combines quantitative and qualitative methods in a mixed research approach, incorporating specialized bibliographic sources, legislative analysis, and field research with participant observation and survey techniques. The results indicate that Sobral has met key requirements related to selective collection and the operation of recycling cooperatives; however, there is a need to strengthen public participation and promote both formal and informal environmental education in the medium and long term to achieve a more effective and continuous policy. Furthermore, integrated public policy management is essential for achieving more effective and sustainable results.